2017
DOI: 10.1021/acsami.7b07735
|View full text |Cite
|
Sign up to set email alerts
|

Light and Strong Hierarchical Porous SiC Foam for Efficient Electromagnetic Interference Shielding and Thermal Insulation at Elevated Temperatures

Abstract: A novel light but strong SiC foam with hierarchical porous architecture was fabricated by using dough as raw material via carbonization followed by carbothermal reduction with silicon source. A significant synergistic effect is achieved by embedding meso- and nanopores in a microsized porous skeleton, which endows the SiC foam with high-performance electromagnetic interference (EMI) shielding, thermal insulation, and mechanical properties. The microsized skeleton withstands high stress. The meso- and nanosized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
92
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(94 citation statements)
references
References 47 publications
2
92
0
Order By: Relevance
“…Porous silicon carbide (SiC) monoliths attract increasing attentions in catalyst/catalyst support, electromagnetic absorption, heat exchanger, hot gas separation, porous media combustion, and metal/ceramic composite areas, owing to their excellent properties including high‐temperature stability, good mechanical strength, low thermal expansion coefficient, high thermal conductivity, and chemical inertness. In light of their promising applications, numerous methods have been developed for the fabrication of porous SiC monoliths, such as oxidation bonding, freeze‐drying, sacrificial templating, direct foaming, and sol‐gel method combined with carbothermal reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Porous silicon carbide (SiC) monoliths attract increasing attentions in catalyst/catalyst support, electromagnetic absorption, heat exchanger, hot gas separation, porous media combustion, and metal/ceramic composite areas, owing to their excellent properties including high‐temperature stability, good mechanical strength, low thermal expansion coefficient, high thermal conductivity, and chemical inertness. In light of their promising applications, numerous methods have been developed for the fabrication of porous SiC monoliths, such as oxidation bonding, freeze‐drying, sacrificial templating, direct foaming, and sol‐gel method combined with carbothermal reduction.…”
Section: Introductionmentioning
confidence: 99%
“…However, EM waves penetrate through the composite wherein, waves get interacted with the trapped nanoparticles + MWNTs present in the composites. This leads to the magnetic and ohmic losses resulting in resulting in dissipation of EM waves and energy absorption of EM waves ,. The surviving EM waves penetrate in the polymer composites containing 3 wt% MWNTs and phenomena of EM waves attenuation repeats.…”
Section: Charge Transportmentioning
confidence: 99%
“…Silicon carbide (SiC) foams have a number of unique characteristics such as low density, low thermal conductivity, controlled permeability, high surface area, high thermal shock resistance, high specific strength, good oxidation resistance, and ability to absorb electromagnetic waves . These unique characteristics make them suitable for application as a thermal shield in aerospace, light‐weight structural component for high‐temperature applications and electromagnetic interference (EMI) shielding at high temperature .…”
Section: Introductionmentioning
confidence: 99%
“…Liang et al reported a preparation of SiC foam from dough by carbonization followed by carbothermal reduction. They obtained SiC foams with hierarchical pore structure having a maximum porosity of 78% …”
Section: Introductionmentioning
confidence: 99%